Apoptosis and necroptosis in the liver: a matter of life and death. Issue 12 (December 2018) - Schwabe, Robert; Luedde, Tom
Abstract Cell death represents a basic biological paradigm that governs outcomes and long-term sequelae in almost every hepatic disease condition. Acute liver failure is characterized by massive loss of parenchymal cells but is usually followed by restitution ad integrum. By contrast, cell death in chronic liver diseases often occurs at a lesser extent but leads to long-term alterations in organ architecture and function, contributing to chronic hepatocyte turnover, the recruitment of immune cells and activation of hepatic stellate cells. These chronic cell death responses contribute to the development of liver fibrosis, cirrhosis and cancer. It has become evident that, besides apoptosis, necroptosis is a highly relevant form of programmed cell death in the liver. Differential activation of specific forms of programmed cell death might not only affect outcomes in liver diseases but also offer novel opportunities for therapeutic intervention. Here, we summarize the underlying molecular mechanisms and open questions about disease-specific activation and roles of programmed cell death forms, their contribution to response signatures and their detection. We focus on the role of apoptosis and necroptosis in acute liver injury, nonalcoholic fatty liver disease (NAFLD), nonalcoholic steatohepatitis (NASH) and liver cancer, and possible translations into clinical applications. Cell death is a fundamental driver of liver disease progression. Here, the authors summarize the specific roles of apoptosis and necroptosis in different liver disease aetiologies, including nonalcoholic fatty liver disease, nonalcoholic steatohepatitis and liver cancer. Key points Cell death is a fundamental driver of liver disease progression to liver fibrosis, cirrhosis and hepatocellular carcinoma. Depending on the underlying disease entity, distinct forms of programmed cell death and cell death response pathways can be activated in the liver. Necroptosis is a new form of programmed cell death that is activated by the necrosome, which consists of the kinases receptor-interacting serine/threonine-protein kinase 1 (RIPK1) and RIPK3 and the pseudokinase mixed lineage kinase domain-like protein (MLKL). Despite necroptosis being challenging to detect in vivo, there is accumulating evidence that this cell death form is a pathogenically relevant driver in several liver diseases that were associated with apoptosis. Necroptosis seems to be particularly important in nonalcoholic fatty liver disease, nonalcoholic steatohepatitis and liver cancer but does not contribute to acetaminophen toxicity or ischaemia–reperfusion injury. A better functional characterization of necroptosis in liver disease models might lead to novel therapeutic strategies that target necroptosis to prevent the progression and decompensation of chronic liver disease.